2014
DOI: 10.4103/0973-6131.123478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga training and detraining on respiratory muscle strength in pre-pubertal children: A randomized trial

Abstract: Objective:To evaluate the effect of yoga on forced vital capacity (FVC), forced expiratory volume in Ist second (FEV1), peak expiratory flow rate (PEFR), FEVI/FVC ratio, and pulmonary pressures [maximum inspiratory pressure (MIP), maximum expiratory pressure (MEP) at the end of 3 months yoga training and the detraining effect on the above parameters in 7-9-years-old school going children.Materials and Methods:A total of 100 participants were recruited from a school in Bangalore. After baseline assessments, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…37 Objective data collected from school records and academic tests have shown postintervention improvements in student grades 74 and academic performance. 42 Furthermore, physiological and cognitive outcome measures reported in a few studies have found decreased cortisol concentrations 73 and improvements in cognitive planning and execution, 39 micronutrient absorption, flexibility, grip strength, abdominal strength, 70 respiratory muscle strength, 62 heart rate variability, 60 and stress reactivity, as determined by skin conductance responses. 79 This review has focused exclusively on studies assessing student outcomes; however, it is important to note that a handful of studies have evaluated the effects of yoga interventions for classroom teachers.…”
Section: Review Of Research On School-based Yoga Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Objective data collected from school records and academic tests have shown postintervention improvements in student grades 74 and academic performance. 42 Furthermore, physiological and cognitive outcome measures reported in a few studies have found decreased cortisol concentrations 73 and improvements in cognitive planning and execution, 39 micronutrient absorption, flexibility, grip strength, abdominal strength, 70 respiratory muscle strength, 62 heart rate variability, 60 and stress reactivity, as determined by skin conductance responses. 79 This review has focused exclusively on studies assessing student outcomes; however, it is important to note that a handful of studies have evaluated the effects of yoga interventions for classroom teachers.…”
Section: Review Of Research On School-based Yoga Interventionsmentioning
confidence: 99%
“…A total of 47 publications met the search criteria and were analyzed (Table ). Publications of therapeutic clinical trials conducted in a school setting but not included in the analysis included studies of yoga in students with special educational needs or disabilities and/or emotional, behavioral, and learning difficulties, including attention deficits and autism spectrum disorders, visual impairment, asthma, poor coordination, and mental retardation .…”
Section: Review Of Research On School‐based Yoga Interventionsmentioning
confidence: 99%
“…Only those students were selected that satisfied the selection criteria. Outcome measures: a) Student checklist filled by both teachers and their parents [27].…”
Section: Subjectsmentioning
confidence: 99%
“… 20 It has received much attention from the scientific communities over the last 20 years due to its effectiveness in enhancing muscular strength, endurance, body flexibility, 21 generating balanced energy, vitality, 22 and cultivating calmness in the mind. 23 Also, Yoga has been observed to have good benefits on health related fitness in sighted school children’s muscles strength, 24 - 26 endurance, 24 , 25 flexibilty, 24 and cardiovascualr endurance. 24 Its positive effects in children with visual impairment are also well-documented, including autonomic arousal, 27 balance, 28 and proprioception.…”
Section: Introductionmentioning
confidence: 99%